Landslide Hazard Zoning in Bijar Town Using Analytical Hierarchy Method (AHP) - Musa Abedini; Bahareh Ghasemyan (نشریه جغرافیا و برنامه‌ریزی, 2015)
Landslides and mountainside instabilities are major dangers for human activities which often cause the waste of economic resources and damage to properties and installations. These dangers occur in natural slopes or in slopes changed by man. This study mainly aims at identifying the factors influencing landslides happening in the city of Bijar, Kordestan Province, and at evaluating the regions having the potentiality of landslide for preparing localization map using the analytical hierarchy process (AHP) Model. In the present study, first employing field visits, questionnaires, geological and topographic maps, and reviewing the studies carried out, nine factors including the variables of: height from the sea level, degree of slope, direction of slope, geology, the distance from the linear elements (fault, road, river), rainfall, and land use were employed. Then affecting factors were binary compared using analytical method by indicating the weight of each factor as indicator for their effects in occurrence of landslide. Accordingly, the landslide zonation hazard map was prepared to the use of weighed information layer and weighted coefficient of each factor. Results of this study show That slope factor of the relative weight of 0.307, and Landuse factor with the relative weight of 0.218 The most effective respectively And the relative weight of rainfall factor 0.019 the lowest impact on Landslides have on the city of Bijar. Thus, 75.489 % of the area of the region have faced very low-risk, 10.037% with low risk, 3.628% with average risk, 4.062% with high risk, and 6.784% with very high risk.